Religious Beliefs, Treatment Seeking, and Treatment Completion among Persons with Substance Abuse Problems - Kesha Baptiste-Roberts; Niya Werts; Kimberly Coleman; Mian Hossain (Addiction and Health, 2021)
Background: Religious beliefs can assist with the success of treatment in persons with substance abuseproblems by providing social support, confidence, and hope.Methods: As such, a secondary analysis using 2013 National Survey on Drug Use and Health (NSDUH), of20219 participants with self-identified illicit substance use problems was conducted. Survey was weightedbivariate and multivariate regression analysis was used to adjust for potential confounders.Findings: Approximately, 15.0% of the study sample were between ages of 18-25 years and 71.5% wereNon-Hispanic Black, 11.3% were Non-Hispanic White, and 12.1% were Hispanic. About 10.3% had less than ahigh school education, 28.0% graduated high school, 30.0% had some college education, and 32.0% werecollege graduates. Only 1.3% reported receiving substance abuse treatment in the past 12 months and5.4% perceived a need for substance abuse treatment in the last 12 months. 65.0% reported that religiousbeliefs were an important part of their life and 62.5% reported that their religious beliefs influenced theirdecision making. After adjustment for sociodemographic factors, both the importance of religious beliefs andthe influence of religious beliefs on decision making were associated with increased odds of having treatment[odds ratio (OR) = 1.56, 95% confidence interval (CI): 1.14-2.14 and OR = 1.51, 95% CI: 1.11-2.05, respectively].However, there was no association between the importance of religious beliefs or the influence of religiousbeliefs on decision making and perceived need for substance abuse treatment.Conclusion: These findings suggest that religious beliefs may be an important determinant in receiving treatmentamong substance abusers and also have implications for exploration of faith-based and faith-placed interventions